Contrasting the Principles behind the Orientation of Building Forms and Location of Spatial Components around the Globe (Journal of Science and Technology, 2016)
Building designers are advised to use sustainable design measures in order to make spaces comfortable, before applying mechanical systems. An important aspect of sustainable design is orientation, specifically the rule to orient buildings to the north and south. However, in an attempt to employ this sustainable principle, various cultures resort to different myths as means of justification. The paper presents historical and modern views and theories on orientation of building forms, spatial components, and the surrounding myths worldwide. The results showed that even though the recommended orientation is mostly the north-south, the myths around this measure are sometimes rooted in the culture of places. For instance, the Chinese, many of whom practice the Feng Shui theory, support design recommendations that follow the flow and balance of positive (yang) and negative (yin) energies. Furthermore, room heights between 3 and 3.5 metres, centrally placed dining spaces and main entrance to buildings in the South are common principles worldwide.